Androgenesis in tomato (Solanum lycopersicum L.)-Effect of genotypes, microspore development stage, pre-treatments and media composition on induction of haploids - Kambale, Rohit; Ramasamy, Gnanam; Balasubramanian, Rajagopal; Thiruvenkatasamy, Saraswathi; Sekar, Vinusri (Journal of Phytology, 2023)
Doubled haploid (DH) technology remarkably accelerates the crop breeding by obtaining homozygous lines in a single generation. The present study was targeted in generating haploid plants through androgenesis. Anthers from immature flower buds of six tomato genotypes viz., LE-1230, LE-1236, LE-1256 TLCV 2, PKM 1 and TNAU tomato hybrid CO 3 were used for induction of haploids. A preliminary study based on callus induction frequency (CIF), more than 5% was helpful in short listing flower bud size, pre-treatments and growth regulator combinations. Subsequently, anthers from two different sized flower buds (4 and 6 mm length), dissected either from fresh or pre-treated flower buds (2 and 5 days in dark at 4 °C or gamma irradiated) were inoculated in MS medium fortified with different growth regulators for callus induction. Among the genotypes, TLCV 2 had recorded the maximum CIF (38.80%) from anthers of 4 mm long flower buds followed by TNAU tomato hybrid CO 3 (34.70%). Throughout the study, anthers from 4 mm long flower buds responded the best for callus induction. Among the pre-treatments, anthers from gamma irradiated flower buds recorded the highest CIF (31.90%) when compared to others. Cold shock (4 °C) in dark to flower buds for 2 days had improved the CIF of anthers when compared to fresh in LE 1230, LE 1238, TLCV2 and TNAU tomato hybrid CO 3, but when the cold shock was increased to 5 days, invariably there was a reduction in CIF in all the six genotypes. TA 8 (MS + 2iP (0.5 mg L-1) + NAA (0.5 mg L-1)) medium was found to be the best for maximum CIF in LE 1230 and PKM1, TA1 (MS + 2iP (1.0 mg L-1) + IAA (2.0 mg L-1)) in LE 1238, LE 1256 and TNAU tomato hybrid CO 3 and TA7 (MS + 2iP (0.5 mg L-1) + Kinetin (1.5 mg L-1) + NAA (1.0 mg L-1)) for TLCV 2 genotypes. The callus induced was sub cultured at monthly intervals in the same medium for proliferation and later transferred to regeneration medium. A good number of shoots got regenerated only from anther calli of TNAU hybrid CO 3 that was sub cultured in MS medium fortified with Zeatin (0.5 mg L-1). The clumps of shoots induced were separated and inoculated in MS medium supplemented with GA3 (0.5 mg L-1) for shoot elongation. After 4-6 weeks, the elongated shoots were transferred to half strength MS medium enhanced with IBA (1 mg L-1). Profuse rooting from the base of the shoot was noticed in 4-5 weeks. The stomatal count with leaves from the diploid plants and in vitro plants observed were 3-4 and 1 respectively indicating the haploidy nature of in vitro plants.